Detection of moving point symbols on cartographic backgrounds - Vassilios Krassanakis; Vassiliki Filippakopoulou; Byron Nakos (Bern Open Publishing, 2016)
The present paper presents the performance of an experimental cartographic study towards the examination of the minimum duration threshold required for the detection by the central vision of a moving point symbol on cartographic backgrounds. The examined threshold is investigated using backgrounds with discriminant levels of information. The experimental process is based on the collection (under free viewing conditions) and the analysis of eye movement recordings. The computation of fixation derived statistical metrics allows the calculation of the examined threshold as well as the study of the general visual reaction of map users. The critical duration threshold calculated within the present study corresponds to a time span around 400msec. The results of the analysis indicate meaningful evidences about these issues while the suggested approach can be applied towards the examination of perception thresholds related to changes occurred on dynamic stimuli.